Adsorption of Bromothymol Blue Dye onto Bauxite Clay (Baghdad Science Journal, 2024)
The goal of the current work is to use an inexpensive, non-toxic material with a high water absorption capacity, bauxite clay, to adsorb the bromothymol blue dye from an aqueous solution. In the production of textiles, leather, paint, food, cosmetics, and pharmaceuticals, synthetic organic compounds are used as dyes almost exclusively in modern industrial processes. Because to their harmful side effects, which include their inherent carcinogenicity, toxicity, and mutagenicity as well as the results of their biological transformation, these dyes pose a serious hazard to the environment when they are released. Clay minerals are valuable as depolluting agents due to their swelling potential, colloidal behavior, and adsorption capacity. The adsorption behavior of bromothymol blue dye from an aqueous solution was studied using bauxite clay. Different variables such as contact time, dosage, ionic strength, and temperature were studied to show the effect on bromothymol blue adsorption onto bauxite clay from an aqueous solution using the batch adsorption method. This study showed that the adsorption decreased by increasing the temperature (15–40 C) and increased by increasing the clay weight from 0.2 to 1.6 g. It also showed as the amount of time rose, the adsorption grew until it reached an equilibrium time of 155 minutes. Thermodynamic metrics including change in free energy (∆G), enthalpy (∆H), and entropy (∆S) all were assessed. A positive correlation was found between the absorbance and the range of concentrations of bromothymol blue (4–32 g/mL) with a correlation coefficient of 0.9911. The maximum wavelength was found and set to 432 nm for all measurements